A computer model study of multiphase chemistry in the Arctic boundary layer during polar sunrise - Michalowski, BA; Francisco, JS; Li, S. M.; Barrie, L. A.; Bottenheim, J. W.; Shepson, PB (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2000)
A multiphase chemical box model of Arctic halogen chemistry has been developed using a PC-based modeling program developed by Environment Canada called the Chemical Reactions Modeling System(CREAMS). The multiphase model contains 125 gas phase reactions, 19 photolysis reactions, and 16 aqueous reactions occurring in suspended aerosol particles and the quasi-liquid component of snow. The model simulates mass transfer of species between the gas phase and particles, and between the gas phase and the snowpack. Model simulations were conducted for the Arctic for the period April 16 to April 24 at 245 K within a 400 m boundary layer. The complete model simulates halogen-catalyzed ozone depletion within 5 days from the start of the model run, via known gas and heterogeneous phase activation mechanisms. A critically important model reaction is BrO + HCHO –> HOBr + CHO, which has a substantial impact on gas phase HOBr, and subsequent condensed phase chemistry. When coupled with a necessary snowpack efflux of aldehydes, required to maintain the aldehyde concentrations at observed levels, the new BrO chemistry has a significant impact on the concentrations of gas phase bromine species, particle bromide, and chlorine atoms, through chemistry occurring in the snowpack. We also find that O-3 depletion cannot be simulated without the presence of heterogeneous halogen chemistry occurring in the snowpack and that the rate of O-3 depletion is limited by the mass transfer rate of HOBr to the snowpack.